PENDAMPINGAN PENGELOLAAN LEARNING MANAGEMENT SYSTEM BERBASIS MOODLE UNTUK GURU DAN SISWA DI SMA NEGERI 1 SUKAWATI - A. A. Istri Ita Paramitha; Eka Grana Aristyana Dewi; I Nyoman Yudi Anggara Wijaya; Kadek Oki Sanjaya (JURNAL SEWAKA BHAKTI, 2022)
SMA Negeri 1 Sukawati is a higher school located on Jl. Lettu Wayan Sutha, Batuan Village, Kec. Sukawati, Gianyar. SMA Negeri 1 Sukawati, commonly known as SUKSMA, is one of the favourite schools which is popular in the society. SUKSMA has 129 teachers from various fields of study. The information technology facilities for the students are quite good. It has four computer laboratory rooms, which has 150 computers in total. Besides, they have 5 IT staffs in charge of assisting activities related to information technology at SUKSMA. However, the use of these IT facilities is inefficient due to the teacher skill using technology to manage their e-learning. This is the background for researchers to carry out community service activities in the form of mentoring the management of the Moodle-based Learning Management System (LMS) at SMA Negeri 1 Sukawati. This activity is conducted to help the teacher and the student so that they could manage the Moodle-based LMS at SMA Negeri 1 Sukawati.